Incremental vs. Breakthrough Innovation: The Role of Technology Spillovers - Byun, Seong K.; Oh, Jong-Min; Xia, Han (Management Science, 2021)
We show that technology spillovers shift the composition of corporate research and development by promoting innovation based on the exploitation of existing knowledge while disincentivizing innovation that explores new areas and breaks new ground. Accordingly, firms facing large technology spillovers attain fewer superstar inventors among their human capital, who are important drivers of breakthrough technology advancement. These findings complement the existing studies documenting the positive effect of technology spillovers in increasing firms’ overall innovation outputs; they highlight potential downsides of technology spillovers in reducing firm investment in technology breakthrough and valuable human capital. This paper was accepted by Gustavo Manso, finance.